2021
DOI: 10.1111/aos.14926
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of preserved versus preservative‐free beta‐blockers in patients with glaucoma or ocular hypertension: a systematic review

Abstract: Preservative‐free topical medications have been introduced for glaucoma care to reduce ocular adverse events associated with preservatives. This is a systematic review and meta‐analysis of randomized clinical trials (RCTs) comparing the efficacy and safety of beta‐blockers, or combination using beta‐blockers, with and without preservatives. PubMed, EMBASE and Web of Science were examined. Risk of bias was assessed using the Cochrane Handbook for Systematic Reviews. The primary outcome was change in intraocular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In the meta-analysis, the level of evidence for all ocular surface outcomes was low or very low and reported in only a few studies. No significant difference was observed in ocular surface symptoms [10].…”
Section: Adverse Effectsmentioning
confidence: 74%
See 1 more Smart Citation
“…In the meta-analysis, the level of evidence for all ocular surface outcomes was low or very low and reported in only a few studies. No significant difference was observed in ocular surface symptoms [10].…”
Section: Adverse Effectsmentioning
confidence: 74%
“…The difference in mean IOP changes between preservative-free and preservative-containing formulations was statistically significant, but of no clinical importance (MD 0.29 mmHg; 95% confidence interval 0.07-0.51 mmHg; p = 0.010). In 6 out of 7 studies, slightly lower IOP was reported in patients using preservative-containing formulations [10].…”
Section: Efficacy Of Medicines Containing Preservativesmentioning
confidence: 98%
“…Glaucoma is a complex disease with no effective cure. Glaucoma is usually treated with prescription eye drops that function via different molecular mechanisms, including prostaglandin analogs (latanoprost, travoprost, bimatoprost, and tafluprost) ( Aihara, 2021 ), β-blockers ( Skov et al, 2021 ), α-adrenergic agonists ( Nocentini and Supuran, 2019 ), cholinergic inhibitors, carbonic anhydrase inhibitors ( Jansook et al, 2021 ) and cholinergic drugs ( Faiq et al, 2019 ). These eye drops reduce IOP by improving the outflow of AH through the trabecular drainage system or by reducing the volume of AH produced by the eye.…”
Section: Progress and Prospects For Research On Glaucoma Treatment Ta...mentioning
confidence: 99%
“…Typically, medication is the preferred treatment choice for patients with glaucoma [ 18 ]. In recent decades, several small-molecule agents, such as cholinergic agents [ 19 , 20 ], beta-adrenergic agonists [ 21 , 22 ], alpha-adrenergic agonists [ 23 ], beta-blockers [ 24 , 25 ], carbonic anhydrase inhibitors [ 26 ], prostaglandin analogs [ 27 - 29 ], and Rho-associated coiled-coil protein kinase (ROCK) inhibitors [ 30 ], have been developed and used to treat glaucoma. These molecular agents can lower IOP by reducing the rate of AH formation, increasing the outflow of AH from the unconventional outflow pathway, or decreasing the outflow resistance of AH in the conventional outflow pathway [ 23 ].…”
Section: Introductionmentioning
confidence: 99%